Knowledge About Medical Equipment Attached to Their Children and Coping Strategies Among Mothers During Hospitalization in the NICU at Waled Regional General Hospital, Cirebon Regency - Terry Melani (INDOGENIUS, 2026)
Background & Objective: Transitional conditions and adaptation in neonatal and perinatal is a period that can cause physiological changes and even death. In this condition, the baby needs intensive care in a special room. BBL installed various medical devices during treatment at the NICU. The number of BBL treated at the NICU in January to December 2024 was 226 people and those who experienced deaths were 100 people. This has become a stressor and has changed coping especially for mothers as long as their children experience hospitalization. This study aims to determine the relationship between knowledge about medical devices installed on their children and coping strategies on mothers during hopitalization in Waled Hospital Cirebon District. Method: The type of research used is descriptive correlational with prospective approaches. The sampling technique used a total sample of 19 respondents during May to June 2025 at the Waled Hospital in Cirebon. The statistical test used is Spearmen Rank. Result: The results obtained r value of 0.686 and p value <∝ means that Ho is rejected, then there is a strong and positive relationship between knowledge of medical devices installed on their children and coping strategies on mothers during hopitalization in Waled Hospital Cirebon Regency (p value = 0.001, ∝ = 0.05 r = 0.686). Conclusion: Knowledge of medical equipment installed in their children can be given continuously to mothers through health education and provision of counseling so that maternal coping strategies become adaptive during hospitalization of their children.